La libertad de los esclavos frente a la legislación y las ideas antiesclavistas en el Nuevo Reino de Granada entre la segunda mitad del siglo XVIII y comienzos del XIX (2013)
This article explores the legal resources which black slaves counted on in order to improve his life style or to obtain his freedom in the New Kingdom of Granada in the light of the Spanish legislation (metropolitan or viceregal) between the middle of eighteenth century and at the beginning of the nineteenth century. Furthermore, a “poll” was carried out in the New Granada people concerning their anti-slavery thoughts during that time.